2017
DOI: 10.1530/ec-17-0239
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal hyperandrogenism does not deteriorate insulin resistance and lipid profile in women with PCOS

Abstract: ObjectiveThe aim of this study was to investigate the impact of adrenal hyperandrogenism on insulin resistance and lipid profile in women with polycystic ovary syndrome (PCOS).Patients and methodsWe studied 372 women with PCOS according to the NIH criteria. 232 age- and BMI-matched women served as controls in order to define adrenal hyperandrogenism (DHEA-S >95th percentile). Then, patients with PCOS were classified into two groups: with adrenal hyperandrogenism (PCOS-AH, n = 108) and without adrenal hyperandr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Another crucial steroid hormone produced by the adrenal cortices is DHEA-S [41], which together with dehydroepiandrosterone (DHEA) is the most abundant circulating steroid hormone in the human body [42]. The association between DHEA-S concentration and metabolic disturbances during PCOS is controversial [43]. A study conducted by Paschou et al [43] revealed that the concentration of DHEA-S was not associated with significant alteration in lipids profile parameters, despite the higher concentrations of TT and AD, whereas a study conducted by Meirow et al [44] showed that the concentration of DHEA-S was positively correlated with the level of CHO, LDL-C, and TG, and negatively with HDL-C in the blood of patients with IR.…”
Section: Discussionmentioning
confidence: 99%
“…Another crucial steroid hormone produced by the adrenal cortices is DHEA-S [41], which together with dehydroepiandrosterone (DHEA) is the most abundant circulating steroid hormone in the human body [42]. The association between DHEA-S concentration and metabolic disturbances during PCOS is controversial [43]. A study conducted by Paschou et al [43] revealed that the concentration of DHEA-S was not associated with significant alteration in lipids profile parameters, despite the higher concentrations of TT and AD, whereas a study conducted by Meirow et al [44] showed that the concentration of DHEA-S was positively correlated with the level of CHO, LDL-C, and TG, and negatively with HDL-C in the blood of patients with IR.…”
Section: Discussionmentioning
confidence: 99%
“…PCOS is accompanied by a higher incidence of hypertension, insulin resistance and lipid profile abnormalities, resulting in an adverse cardiovascular profile (812); a higher prevalence of glucose dysregulation, manifesting as impaired fasting glucose or type 2 diabetes (13, 14); and obesity. However, it is recognized that within the PCOS phenotype there are a number of different androgenic and insulin resistant profiles (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…The excessive androgens from ovaries are considered as the most crucial inducer of PCOS [5] , although adrenal hyperandrogenism emerges in 20-30% PCOS women. [48] Statins are supposed to act primarily on the ovaries. First, statins had been con rmed not to take any effects on androgen levels in postmenopausal women, in whom it is wellknown that the major origin of androgens is extra-ovarian.…”
Section: Discussionmentioning
confidence: 99%